Worker Churn and Employment Growth at the Establishment Level - Rüdiger Bachmann; Christian Bayer; Christian Merkl; Stefan Seth; Heiko Stüber; Felix Wellschmied (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We find that worker turnover is more procyclical than job turnover. Procyclical worker churn result almost exclusively from job-to-job transitions. The size and cyclical properties of churn are close to uniform along the entire employment growth distribution of establishments. Even shrinking firms churn, i.e., they hire while separating from workers. The cyclical movements in the source of hiring, from employment vs non-employment, are close to uniform across the employment growth distribution.
Keywords: E32; J23; J63; 330